Pengaruh Umur Perusahaan, Ukuran Perusahaan, Dan Kualitas Manajemen, Terhadap Resiko Investasi Di Perusahaan Perbankan Yang Listing Di Bei Tahun 2021-2023 - Roy Saleh; Arubina Bangsawan; Irsan; Kemas Welly Angga Permana (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2024)
This research aims to examine the influence of company age, company size and management quality on the investment risk of banking companies listed on the Indonesia Stock Exchange (BEI) during the 2021-2023 period. The analysis method used is multiple linear regression with the help of SPSS software. This research uses quantitative methods. This research uses secondary data. The number of samples used was 60. The data analysis techniques used in this research include: Descriptive statistical analysis, then carrying out classical assumption tests in the form of normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests. The results obtained from this research are: (1) Company age (X1) has a positive effect on investment risk (Y); (2) Company Size (X2) has a positive effect on Investment Risk (Y); (3) Management Quality (X3) has a positive effect on Investment Risk (Y); (4) Company Age (X1), Company Size (X2), and Management Quality (X3) have a positive effect on Company Value (Y)